Body image and disordered eating behaviors in Hispanic/Latino Youth: Findings from the Hispanic Community Health Study/Study of Latino Youth. (1st August 2022) - Cordero, Christina; Pulgaron, Elizabeth R.; Marchante-Hoffman, Ashley N.; Llabre, Maria M.; Perreira, Krista M.; Sotres-Alvarez, Daniela; Isasi, Carmen R.; Elder, John P.; Delamater, Alan M.
Abstract: Background: Prevalence of certain disordered eating behaviors is higher among Hispanic youth compared to non-Hispanics. Understanding the role of body image and social attitudes towards weight in disordered eating may inform treatment in Hispanic youth. Methods: We analyzed data from the Hispanic Community Health Study/Study of Latino Youth (SOL Youth). Our sample included 1, 463 children aged 8–16 years from four sites (Bronx, Chicago, Miami, San Diego) assessed in 2011–2014. Body image discrepancy score was calculated as the difference between perceived ideal body image and actual body image using two numbered visual graphs: adolescent (n = 728) or child (n = 735), each with slightly different scales. Questionnaires measured influences from social attitudes toward weight and disordered eating behaviors. Three disordered eating behaviors (dieting, overeating, and compensatory behaviors) were analyzed as the dependent variable. Logistic regression models adjusted for age, sex, acculturative stress, and field center to estimate adjusted odds ratios (aOR) and 95% confidence intervals (CI). Results: Mean body image discrepancy score was −0.79 for adolescents (SE = 0.08) and −0.50 for children (SE = 0.05), with a negative score signifying a perceived actual body image larger than their ideal. Body image discrepancy was strongly associated with dieting (dieting ≥5 times/year aOR = 0.64, 95% CI 0.53, 0.77) and compensatory behaviors (aOR = 0.65, 95% CI 0.50, 0.85) among adolescents, and was strongly associated with overeating among children (aOR = 0.74, 95% CI 0.61, 0.91). Significant associations were not observed with social attitudes towards weight. Conclusions: Associations observed with body image discrepancy and disordered eating behaviors can inform interventions in Hispanic/Latino youth, which should consider acculturative stress.